PENGARUH PEMBERIAN SUSU KEDELAI TERHADAP KADAR HEMOGLOBIN IBU NIFAS - Yulaikah, Siti; Susilowati, Dewi; Febriana, Nafis Maeda (Jurnal Kebidanan, 2025)
Background, Decrease hemoglobin levels often happened to the mother postpartum, especially in the first week First post childbirth. Condition This can cause disturbance recovery post giving birth, slowing down the healing process wound, improve risk infection, as well as hinder production of breast milk (ASI). One of the alternatives that can used For overcome problem This is with non- pharmacological approach. Soy milk is one of source vegetable containing​ substance iron, protein, fat, and beneficial isoflavones​ for health, and potentially help increase hemoglobin levels in blood. Research purposes, for know influence soy milk giving to hemoglobin levels in mothers postpartum. Research methods, Study This use quasi- experimental design with approach two group pretest-posttest . The sample consists of from 30 mothers postpartum , divided into two groups , namely 15 people each intervention and 15 people group control , using technique purposive sampling . Group intervention given 250 ml of soy milk every Morning for 7 days . Data analysis was carried out with the t-test. Research Results, Average increase hemoglobin levels in the group intervention of 1.3 gr/dl ± SD 0.16 with mark p = 0.000, which indicates existence significant influence .​ Conclusion, Giving soy milk influential significant to improvement hemoglobin levels in mothers postpartum